Young Shorty Again: The Fair - Webster, James (Ginn and Company Ltd, 1981)
The six book in shorty the puppy form the first stage, and The Rescue in young shorty Books is the immediate sequel to the sequence of stories in shorty the puppy.
Keywords: Juvenile literature-Fiction